PENGGUNAAN ANTIBIOTIK PROFILAKSIS DENGAN METODE GYSSENS PADA PASIEN BEDAH ORTOPEDI DI RUMAH SAKIT X PROVINSI BANTEN - Arrang, Jesica; Setiawan, Benny; Pramitaningastuti, Anastasia Setyopuspito (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Surgical wound infection (ILO) is one type of nosocomial infection that is commonly found in healthcare delivery in developing countries. Although most surgical patients receive prophylactic antibiotics, the incidence of ILO in orthopaedic surgery patients is still high. Therefore, it is necessary to evaluate the use of prophylactic antibiotics using the Gyssens method for orthopaedic surgery patients. This study is observational and retrospective data obtained from medical records of orthopedic surgery patients (Total Knee Replacement, Total Hip Replacement and Open Reduction, Internal Fixation) Hospital